Corporate community involvement : the definitive guide to maximizing your business' societal engagement - Lakin, Nick.; Scheubel, Veronica (Stanford, Calif. : Stanford University Press ; Sheffield, UK : Greenleaf, 2010)
The book's advice is backed by inspiring interviews with best-in-class practitioners from businesses like Microsoft, GlaxoSmithKline, Ericsson- as well as leading experts in corporate responsibility and community involvement. The text highlights best-practice approaches, effective methods, and concise tools to help managers "get there faster" and "get it right first time." The core of the book is a step-by-step guide that shows readers how to: conduct a current state analysis and devise a strategy; organize staffing and budgets; integrate corporate community involvement throughout the business and create high-profile programs' partner across sectors; measure and evaluate results; communicate successful activities; and overcome challenges.
Introduction: Corporate Community Involvement: what it is, what it is not -- How to develop the right community, involvement strategy -- Company roles, responsibilities, and skills in Community Involvement -- 'How much does it cost?' How to budget for corporate Community Involvement -- How to manage corporate giving, foundations, and disaster relief -- Integrating Community Involvement into your core business: how to work with operations, marketing, and HR -- Make it stand out: how to create and implement leading Community Involvement programs -- How to manage cross-sector collaboration -- The power of employee involvement -- 'You can't manage what you don't measure' How to measure, evaluate, and report Community Involvement -- 'But why haven't we heard about this before?' Communicating your Community Involvement effectively -- 'I knew it would be worthwhile.' Overcoming challenges and instigating change.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Industrial management -- Social aspects; Strategic planning; Corporations -- Public relations -- Management; Electronic books